Solvent Extraction of Am(III), Cm(III), and Ln(III) Ions from Simulated Highly Active Raffinate Solutions by TODGA Diluted in Aliquat-336 Nitrate Ionic Liquid. Issue 6 (19th September 2018) - Zsabka, Peter; Van Hecke, Karen; Adriaensen, Lesley; Wilden, Andreas; Modolo, Giuseppe; Verwerft, Marc; Binnemans, Koen; Cardinaels, Thomas
ABSTRACT: The extraction behavior of americium(III), curium(III) (minor actinides, MA), fission products (lanthanides (Ln(III)), Mo, Ru, Pd, and Rh), and corrosion products (Zr and Fe) was studied in batch solvent extraction experiments using the room-temperature ionic liquid (IL) Aliquat-336 nitrate ([A336][NO3 ]) and a solvent composed of 0.05 M TODGA in [A336][NO3 ]. From acidic, dilute Ln(III) feed solutions, [A336][NO3 ] extracts nitric acid ( D ≈ 0.5) and partially An(III) as well as Ln(III) ( D Am = 0.02–0.1, D Eu, and D Cm = 0.01–0.04). The influence of the acid concentrations and kinetics on extraction and back-extraction of Ln(III) and An(III) by 0.05 M TODGA in [A336][NO3 ] was investigated using radiotracer-spiked dilute Ln(III) feed solutions. With the solvent composed of 0.05 M TODGA in [A336][NO3 ], D An and D Ln increase as a function of aqueous feed acidity. In the case of a spiked, simulated highly active raffinate (HAR) feed solution, [A336][NO3 ] extracts La(III) ( D La = 1.36), Ru ( D Ru = 1.64), and Pd ( D Pd = 38), while the distribution ratios of other Ln(III) and An(III) were lower than unity. The solvent composed of 0.05 M TODGA in [A336][NO3 ] co-extracted from HAR Zr(IV) ( D Zr > 300), Pd ( D Pd = 206), and Ln(III) ( D Ln > 1, except for Nd(III)), but An(III) were retained in the aqueous phase. The interference caused by the co-extraction of several fission (Zr, Pd, Ru, and Mo) and corrosion (Zr) products, which are present in the HAR at relatively high concentrations, was suppressed using masking agents (oxalic acid and trans -1, 2-diaminocyclohexane- N, N, N', N' -tetraacetic acid, CDTA). In the case of the actual HAR solution, the kinetics were found to be faster compared with the extraction from dilute Ln(III) feed solutions, possibly due to the different aqueous speciation of the Ln(III) and An(III).